1999
DOI: 10.1103/physrevb.60.7170
|View full text |Cite
|
Sign up to set email alerts
|

Correlated domain model of deuterated dipole glass

Abstract: The low-frequency dielectric relaxation of the deuterated rubidium ammonium dihydrogen phosphate ͑DRADP͒ dipole glass was investigated by examining the complex dielectric permittivity above the glass freezing temperature. We show that none of the well-known Debye-type relaxation functions that include the Cole-Cole, Cole-Davidson, and Kohlrausch-Williams-Watts functions adequately describe the observed dielectric relaxation behavior of the DRADP. We then examine the Chamberlin's correlated domain model as a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Furthermore, the significant blocking effect at low temperature may result in trapped “water clusters” and give rise to a dipole glassy behavior. , Indeed, as shown in Figure d, the dielectric relaxation of 1 ·H 2 O in the temperature range of 225–270 K could be well fitted by the Vogel–Fulcher formula that is commonly used in fitting glassy behavior, τ = τ 0 exp­[ E a / k B ( T – T VF )], , where E a is the average fluctuation activation energy, and T VF is the freezing temperature. The fitting results, E a = 0.03 eV and T VF = 192.0 K, suggested that 1 ·H 2 O is more similar to proton dipole glass ( E a ranges from 0.03 to 0.09 eV) , than to amorphous ice ( E a is ca. 0.35 eV and T VF ranges from 116 to 136 K). The fitting of the dipole glass model suggested that the protons trapped by the blocking effect behave as locally correlated dipole microdomains with random dipole directions and broadly distributed sizes, eventually giving a broadly distributed relaxation time. ,, As complements, the anhydrous phase ( 1 ) showed no significant dielectric anomalies, while the deuterated phase ( 1 ·D 2 O) showed a similar thermal and dielectric anomalies (Figures S9 and S10) with a significantly higher T VF (208 K) and a slightly lower E a (0.02 eV, Figure S10).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, the significant blocking effect at low temperature may result in trapped “water clusters” and give rise to a dipole glassy behavior. , Indeed, as shown in Figure d, the dielectric relaxation of 1 ·H 2 O in the temperature range of 225–270 K could be well fitted by the Vogel–Fulcher formula that is commonly used in fitting glassy behavior, τ = τ 0 exp­[ E a / k B ( T – T VF )], , where E a is the average fluctuation activation energy, and T VF is the freezing temperature. The fitting results, E a = 0.03 eV and T VF = 192.0 K, suggested that 1 ·H 2 O is more similar to proton dipole glass ( E a ranges from 0.03 to 0.09 eV) , than to amorphous ice ( E a is ca. 0.35 eV and T VF ranges from 116 to 136 K). The fitting of the dipole glass model suggested that the protons trapped by the blocking effect behave as locally correlated dipole microdomains with random dipole directions and broadly distributed sizes, eventually giving a broadly distributed relaxation time. ,, As complements, the anhydrous phase ( 1 ) showed no significant dielectric anomalies, while the deuterated phase ( 1 ·D 2 O) showed a similar thermal and dielectric anomalies (Figures S9 and S10) with a significantly higher T VF (208 K) and a slightly lower E a (0.02 eV, Figure S10).…”
mentioning
confidence: 97%
“…The fitting results, E a = 0.03 eV and T VF = 192.0 K, suggested that 1 ·H 2 O is more similar to proton dipole glass ( E a ranges from 0.03 to 0.09 eV) , than to amorphous ice ( E a is ca. 0.35 eV and T VF ranges from 116 to 136 K). The fitting of the dipole glass model suggested that the protons trapped by the blocking effect behave as locally correlated dipole microdomains with random dipole directions and broadly distributed sizes, eventually giving a broadly distributed relaxation time. ,, As complements, the anhydrous phase ( 1 ) showed no significant dielectric anomalies, while the deuterated phase ( 1 ·D 2 O) showed a similar thermal and dielectric anomalies (Figures S9 and S10) with a significantly higher T VF (208 K) and a slightly lower E a (0.02 eV, Figure S10).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Glass is well known to show a slow-relaxation dynamics of nonexponential decay with a universality described by either Kohlrausch-Williams-Watts (KWW) stretched-exponential decay function φ(t) = φ 0 exp[−(t/τ ) β ] (0 < β < 1) or Curie-von Schweidler (CvS) power law decay function φ(t) = φ 0 (t/τ ) −α (0 < α < 2) [1][2][3][4][5]. Dipole glass has been introduced as a model system of glass transition, possibly illuminating more details from wider ranges of experimental accessibilities than spin glass systems [6][7][8][9][10].…”
mentioning
confidence: 99%